ANALISIS PENERAPAN GOOD GOVERNANCE DALAM PROSES PERSIAPAN PEMILIHAN KEPALA DESA - Maria Oktavianus Bupu1; Fidentus Didakus Darma Saputra (Jurnal Dialektika Politik, 2024)
Mbomba Village is one of 158 villages in Ende Regency that participated in the 2019 simultaneous village head elections. On 29 January 2019, the village head election took place in Mbomba Village. The stage examined is the preparation stage. There are several processes in the preparation stage, namely notification of the end of the term of office, village head election committee, proposed election cost plan and determination of voters. Through the Proposed Election Cost Plan, the budget for the implementation of the village head election obtained from the regency is 10,000,000 and its allocation and use is by a team from the regency. For funds originating from the Village Fund Budget (ADD) of Rp.5,000,000, the budget is also included in the 2019 RKPDes. This research focuses on analysing the Good Governance concept approach to the implementation of the Pilkades preparation process. This research uses a qualitative method, so that the research conducted seeks to describe the facts in the field. Based on the concept raised to analyse the implementation of the Pilkades preparation process, the Good Governance concept contains several key indicators, namely accountability, participation, and transparency. The first research result is Accountability, where it was found that the notification of the end of the term of office according to the rules before six months was not delivered. This was due to the BPD's term of office ending at the same time as the village head's term of office. Whereas before the end of the term the letter should have been delivered. The second is participation in the formation of the Pilkades committee. It was found that the formation process was only represented by some members of the community. Whereas all components of the community should be involved. Third, transparency related to information on the selection of the Pilkades committee was not publicly disclosed. This is because the BPD has selected individuals who have the potential to become the committee.